Three essays on brazilian labour market : innovation, legislation and macroeconomic policy analysis - Vargas, Juliano (2020)
Tese (doutorado)—Universidade de Brasília, Faculdade de Administração, Contabilidade, Economia e Gestão de Políticas Públicas, Departamento de Economia, Brasília, 2020.